Education of Islamic Religious Values through The Nahdlatul Ulama Student Association Organization Group - Khoirunnisak, Anis; Samsuri, Samsuri (Lembaga Ta'lif wa An-Nasyr (LTN) PBNU, 2022)
The case of terrorism in Indonesia made the younger generation the target of the dogma of religious radicalism, so the younger generation made it a tool for the success of the terrorist movement. Religion-based community organizations are very significant in preventing the dogma of radical movements for students. This study aims to analyze the Nahdlatul Ulama Student Association/Nahdlatul Ulama Women's Association (IPNU/IPPNU) movement's efforts in Banjardowo Village to provide education on Islamic religious values to youth members and the surrounding community. This study uses descriptive qualitative research methods with interviews, observations, and documentation. The research analysis used is descriptive inductive/qualitative. Informants selected for interviews were core management and members of the organization. The results showed that; Analysis of the description of the IPNU/IPPNU student organization in Banjardowo village and the forms of activities of the IPNU/IPPNU student organization in Banjardowo village in providing education on religious values to members and the community was carried out in a planned and systematic manner.